Heinrich Müller (1820-1864) and the entoptic discovery of the site in the retina where vision is initiated. Issue 1 (2nd January 2022) - Werner, John S.; Gorczynska, Iwona; Spillmann, Lothar
ABSTRACT: Heinrich Müller was a nineteenth-century German retinal anatomist who, during his short career, was one of the discoverers of the rod photopigment rhodopsin and neuroglia in the retina, now known as Müller cells. He also described the ocular muscles and double foveae of some birds. An important, but largely neglected, insight by Müller was to combine careful psychophysical measurements and geometrical optics to find the location of the photosensitive layer of the retina in the living eye. Here, we provide translated passages from Müller's (1855 ) publication and compare his entoptic observations with retinal imaging using optical coherence tomography. Müller correctly deduced from his careful experiments that vision is initiated in the photoreceptors located in the back of the retina .